Hubungan Tingkat Pendidikan dan Self Efficacy Dengan Self Managemen pada Pasien Hipertensi di Puskesmas Tamanan - Ratnasari, Dwigita (Jurnal Keperawatan Profesional, 2020)
Background Degenerative disease is an increasing disease in Indonesia and the most common disease found in Indonesia is hypertension. Hypertension is a direct risk factor for the onset of myocardial infarction and cerebrovascular accidents (CVA). The purpose of this study was to determine the relationship between the level of education and self efficacy with self-management in hypertensive patients at Puskesmas Tamanan. This research method uses Cross Sectional research design. The sample in this study were all hypertensive patients at the Tamanan Puskesmas as many as 120 patients. The sampling technique used in this study was using simple random sampling. Data analysis using spearmen correlation test. The results of the analysis data obtained α 0.01, which means that there is a relationship between education, self efficacy and self management. Conclusion Low education levels in patients with hypertension do not become an influence on self efficacy and patient self-management.